2017
DOI: 10.2215/cjn.09740916
|View full text |Cite
|
Sign up to set email alerts
|

Time to Improve Informed Consent for Dialysis: An International Perspective

Abstract: The literature reveals that current nephrology practice in obtaining informed consent for dialysis falls short of ethical and legal requirements. Meeting these requirements represents a significant challenge, especially because the benefits and risks of dialysis have shifted significantly with the growing number of older, comorbid patients. The importance of informed consent for dialysis is heightened by several concerns, including: () the proportion of predialysis patients and patients on dialysis who lack ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Multimodal interventions are needed to improve how oncologists communicate prognosis and to empower older patients and their caregivers to enquire about prognosis, taking into account the racial, cultural, and socioeconomic backgrounds of the patients and caregivers as well as their beliefs, emotions, and fears . In addition, the problem of severe discordance may require broader public health and policy initiatives to assess whether patients are adequately informed to provide consent to potentially toxic treatments . Nonetheless, although avoiding discordance would seem to be clinically intuitive, it is important to note that, unlike patient's perceived prognosis and curability, the association of discordance in beliefs about curability with outcomes is not well studied, and future studies are needed to assess its relationship with outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal interventions are needed to improve how oncologists communicate prognosis and to empower older patients and their caregivers to enquire about prognosis, taking into account the racial, cultural, and socioeconomic backgrounds of the patients and caregivers as well as their beliefs, emotions, and fears . In addition, the problem of severe discordance may require broader public health and policy initiatives to assess whether patients are adequately informed to provide consent to potentially toxic treatments . Nonetheless, although avoiding discordance would seem to be clinically intuitive, it is important to note that, unlike patient's perceived prognosis and curability, the association of discordance in beliefs about curability with outcomes is not well studied, and future studies are needed to assess its relationship with outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Patient surveys suggest the quality of dialysis decision making is often poor and may not meet the standard for informed consent in some circumstances. 22,23 Few patients receive prognostic information or have their preferences elicited, and many are not presented with the option to forgo dialysis. 24,25 Decision aids that incorporate prognostic information along with other expected outcomes could improve the quality of dialysis decision making and reduce variation in dialysis initiation practices.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ESRD do not often have conversations about their prognosis and all of their care options, including conservative, non-dialytic care. 17 There are several barriers to providing palliative care for patients with renal disease. Improving the integration of palliative care and nephrology by increased use of outpatient combined care models and improving training in palliative care for practicing nephrologists and trainees are several possible solutions to this pressing and multifaceted problem.…”
Section: Discussionmentioning
confidence: 99%
“…In a Boston study of patients on dialysis, no patients reported having a discussion of prognosis and, in 60% of cases, the nephrologist stated that they would not have provided a prognosis. 17 In 2014, Bristowe et al sought to establish a training program for nephrologists in ACP. In the preliminary data they collected on patient experience, the investigators identified that only 50% of patients felt that their concerns were taken seriously by their nephrologist, and less than half of patients felt that they had been sufficiently involved in treatment decisions.…”
Section: Developing a New Model Of Palliative Nephrologymentioning
confidence: 99%